Orexin type-1 receptor inhibition in the rat lateral paragigantocellularis nucleus attenuates development of morphine dependence. (17th April 2020) - Rezaei, Zahra; Kourosh-Arami, Masoumeh; Azizi, Hossein; Semnanian, Saeed
Highlights: Morphine injection for 7 days created the development of morphine dependence in LPGi. Development of morphine dependence have shown by naloxone-precipitated morphine withdrawal behaviors. Application of SB-334867 prevented the development of morphine dependence in rats. Abstract: Orexin neuropeptides are involved in opiate-induced physical dependence and expression of withdrawal signs following drug abstinence. Orexin type-1 receptors (OXR1) are expressed throughout the rostroventrolateral medulla (RVLM), particularly in the lateral paragigantocellularis (LPGi) nucleus. The present study examined whether blocking OXR1 in LPGi region could affect the development of morphine dependence and so behavioral manifestations induced by morphine withdrawal in rats. Male Wistar rats weighing 250−300 g were used. In order to induce drug dependence, morphine was injected subcutaneously (s.c.) (6, 16, 26, 36, 46, 56, and 66 mg/kg, 2 ml/kg) at an interval of 24 h for 7 days. Animals were divided into experimental groups in which the orexin type-1 receptor antagonist, SB-334867 (0.2 μl, 3 mM), or its vehicle were injected into the LPGi nucleus for 7 days before each morphine injection. On day 8, naloxone (2.5 mg/kg, i.p.) was administered and morphine withdrawal behaviors were monitored for 25 min. Our results indicated that the inhibition of OXR1 in LPGi nucleus significantly reduces the development of morphine dependence and behavioral signs elicited by the administration of naloxone in morphine-dependent rats.